CHEMICAL SPECIATION OF SOME HEAVY METALS AND HUMAN HEALTH RISK ASSESSMENT IN WATER AROUND MUNICIPAL DUMPSITES IN JOS, BUKURU AND RAYFIELD, PLATEAU STATE, NIGERIA - M. N., MBORINGONG; C. E., ASHANO; A. U.,, LAR; U. H., DIBAL; J. S., ATANGCHO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The impact of solid waste disposal on water quality is gaining importance worldwide due to seepage of toxic metals through the soil into the groundwater. Urbanization, industrialization and changes in our life styles have compounded the problem of solid waste management in Nigeria. Poor waste management threatens the health of humans and animals, particularly those living close to these pollution point sources.The study area covers Jos-Bukuru and environs in North Central Nigeria. This study was aimed at investigating the chemical species present in groundwater as a result of the impact of solid waste dumpsites in the study area and to evaluate the contributions of the dumpsites to the chemical and physicochemical properties of groundwater around the dumps. Five (5) major dumpsites (Bauchi Road Jos, Rukuba Road Jos, Building Materials Market, Rayfield and Bukuru Town) were sampled for this study. Ten water samples from hand dug wells (two from each site) close to the dumpsites and three controls were collected and analysed for chemical composition and further speciation analysis was conducted on the chemical result to assess the various species present in the waters and possible human health related issues. Results show that the mean values of the pH, temperature, EC, TDS, of the water samples all fall within the WHO permissible limits for portable drinking water. Content of trace elements are generally low in the waters but toxic metal species such as Ba+2, Mn+2, Ni+2, Zn+2, Cd+2, and Pb+2 are common to all the water sources. This study shows that different dumpsites have impacted differently on waters in their different environments. There is the need to curtail the excesses of dumping waste in these areas so as not to add to the exiting contents of toxic metal species in the waters.